Manual ilustrado de tratamento dos ferimentos cutâneos descolantes dos membros inferiores - Mendes, José de Arimateia [UNIFESP] (2017)
Introduction: Skin avultions of the lower limbs are progressively more frequent in the daily practice of plastic surgeons. The increasing numbers of motorcycles in the streets and the heavy traffic in large Brazilian cities have contributed largely to the number of this type of injury in the last two decades. The victim of a high-energy trauma in the lower limbs, besides presenting bone fractures, may also have total or partial skin avultion of the lower limb skin. These patients require a long hospital stay, several reconstructive procedures, and integrated multidisciplinary assistance, moreover they will need many months to recover. Objective: To develop an illustrate handbook to optimize treatment of skin avultions of the lower limbs with an organogram created based on the review of the medical literature. Methods: A literature search has shown that there are emerging technologies on tissue regeneration that can be used to treat these patients. These innovations date from the end of the twenty-first century and, once incorporated to the armamentarium of the reconstructive surgeons, these techniques are able to shorten hospital stay and to improve the functional and cosmetic aspect of lower limb reconstruction. Conclusion: An organogram and an illustrate handbook about skin avultion of the lower limbs have been developed to be used by plastic surgeons, which will allow them to access updated management of this type of patients in any Brazilian city.